Analysis of real estate services digitalisation: current situation and development prospects - A. D. Okolnishnikov; A. I. Ukhova; E. V. Krasnov (Вестник университета)
The article analyses the digitalisation of real estate services in Russia. Empirical works of leading analytical agencies and experts’ academic papers in the field of economic sciences has been summarised and sysrematised. The development key indicators of Russian digital economy, digitalisation level of certain service sectors, digital production features and digital consumption which characterise the digital economy development, have been considered. It has been noted that at present the digital services of in real estate services are at an early stage of development due to the small number of market participants who have fully implemented digital services and online technologies in their activities. It has been revealed that most of the stages of real estate services for the sale or purchase of residential property can be partly or fully realised using digital services and online technologies. Generalised characteristics of real estate services digitalisation at present and prospects for its development have been formulated.